2007
DOI: 10.1002/jctb.1678
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid neural model (HNM) for the on‐line monitoring of lipase production by Candida rugosa

Abstract: A mechanistic model was proposed by Gordillo for the representation of lipase production by Candida rugosa, with the bioreactor in batch and fed-batch operation. However, the model was not able to represent the lipolytic activity. The objective of the present study is to propose an efficient hybrid neural-phenomenological model (HNM) for this process. The experimental data used corresponded to fed-batch operation with constant substrate feed rate at 2.8 × 10 −7 ; 5.6 × 10 −7 and 9.7 × 10 −7 kg s −1 . Artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Presently, works based on hybrid neural-phenomenological [38] are being developed by the group as done before with a biotechnological process [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Presently, works based on hybrid neural-phenomenological [38] are being developed by the group as done before with a biotechnological process [39]. …”
Section: Discussionmentioning
confidence: 99%
“…PCA models are also useful, particularly because they provide a simple variable for fault detection and quality control [72]. Neural networks have been used for biomass estimation on their own [2,14,27,30,47] or in combination with other modeling techniques [9].…”
Section: Software Sensorsmentioning
confidence: 99%
“…The application of hybrid semi-parametric models in form of a soft-senor is very attractive for monitoring and both parallel (Lee et al, 2005) and serial (Boareto et al, 2007;Gnoth et al, 2008;Henneke et al, 2005;James et al, 2002;Jenzsch et al, 2007;Psichogios & Ungar, 1992;Schubert et al, 1994a;Silva et al, 2000Silva et al, , 2001von Stosch et al, 2011b) hybrid semi-parametric models find application. It was shown that the performance of a model in which the states and parameters were estimated by Nonlinear Programming (NLP) optimization or Extended Kalman Filter (EKF) approaches was inferior to the performance of a model in which the variable parameters were estimated using neural networks (Psichogios & Ungar, 1992), namely a hybrid semi-parametric model.…”
Section: Soft-sensor -Predictor Methodsmentioning
confidence: 99%
“…for the modeling of yeast fermentations (Beluhan & Beluhan, 2000;Boareto, De Souza, Valero, & Valdman, 2007;Eslamloueyan & Setoodeh, 2011;Mazutti et al, 2010;Peres et al, 2001;Saraceno et al, 2010;Saxen & Saxen, 1996;Schubert et al, 1994aSchubert et al, , 1994b, for modeling of fungi cultivations (Chen et al, 2000;Ignova et al, 2002;Preusting et al, 1996;Silva et al, 2000Silva et al, , 2001Thibault et al, 2000;van Can et al, 1997Wang, Chen, Liu, & Pan, 2010), for modeling of bacteria cultivations (Costa, Alves, Henriques, Filho, & Lima, 1998;Gnoth et al, 2008;Henneke, Hagedorn, Budman, & Legge, 2005;Henriques et al, 1999;James et al, 2002;Jenzsch, Gnoth, Kleinschmidt, Simutis, & Luebbert, 2007;Laursen et al, 2007;Roubos et al, 2000;Thibault et al, 2000;Tholudur & Ramirez, 1999;Zuo, Cheng, Wu, & Wu, 2006;Zuo & Wu, 2000), for modeling of mammalian cell cultivations (Dors et al, , 1996Teixeira et al, 2005;Vande Wouwer et al, 2004), for modeling of insect cell cultivations (Carinhas et al, 2011), for modeling of hybridoma cell cultivations (Fu & Barford, 1995a, 1995b or for modeling the counter-ion fluxes across an ion-exchange membrane in a membrane-supported biofilm reactor …”
Section: Biochemical Engineeringmentioning
confidence: 99%